Late La Tène scabbards with non-ferrous openwork plates - Istenič, Janka (Arheološki vestnik, 2010)
this article looks at a group of swords and associated scabbards from the transition of the Late La tène to the Roman period. Werner (1977) put forward the hypothesis of their Norican origin, while in later publications their production on the territory of the treveri is also presumed.Our research has shown that parts of all four items from Slovenia for which the composition of the metal has been determined, are of pure brass. In view of the fact that the same applies to the three analysed items of this group from Germany and Slovakia, as well as the finding that the name stamp on one of the swords of the group reveals a Latin name, we assume that they were made in a Celto-Roman milieu; their distribution seems to suggest North-eastern ancient Italy as the possible area of their production.